Impact of Preoperative Rectal Misoprostol on Blood Loss during and after Elective Cesarean Delivery: A Randomized Controlled Trial - Sitaula, Sarita; Uprety, DK; Thakur, A; Pradhan, T (Nepal Journal of Obstetrics and Gynaecology, 2017)
Aims:The aim of this study was to evaluate the effect of preoperative administration of rectal misoprostol onblood loss during and after elective cesarean delivery. Methods:It was a randomized trial including 200 women, divided into two groups (group A and group B), who were planned for elective cesarean delivery and didn’t have risk of postpartum hemorrhage (PPH). Group A received 400μg misoprostol per-rectal preoperatively and intravenous infusion of oxytocin after delivery as hospital protocol.Group B received only intravenous infusion of oxytocin. Primary outcome measureswere the estimated amount of intraoperative and postoperative (24 hours) blood loss and changes in hemoglobin levels 48 hours after delivery. Results:Intraoperative and postoperative blood loss in rectal misoprostol and oxytocin group were significantly reducedin comparison to oxytocin only group. Mean blood loss in groupA was 326.9±116.2 mlwhereas; in group B was 397.7±110.1 ml with p value of < 0.001 which was significant.The difference between preoperative and postoperative hemoglobin level after 48 hours was also significant (1.10±0.51 vs 1.35± 0.49 g/dl with p value <0.001). Conclusion: Preoperative rectal misoprostol was found to be an effective measure to reduce the intraoperative and postoperative blood loss during elective cesarean delivery.